2022
DOI: 10.3389/fendo.2022.828839
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Renal Stones and Primary Aldosteronism

Abstract: IntroductionThe association between primary aldosteronism (PA) and nephrolithiasis is still unclear. The hypercalciuria and hypocitraturia of PA patients might be the reason leading to recurrent calcium nephrolithiasis. This study aimed to evaluate the relationship between PA and renal stones, including stone size and density.Materials and MethodsFrom February 2010 to March 2021, we retrospectively collected 610 patients who presented to our medical center with hypertension history, and all these patients, sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Moreover, hyperaldosteronism causes intracellular acidosis, which increases the absorption of citrate in the proximal tubules and induces hypocitraturia ( 9 , 23 ). A global epidemiological study showed that the prevalence of kidney stone disease ranges from 1.7% to 14.8% ( 24 ), while the prevalence of kidney stone disease in patients with PA is approximately 24% ( 12 ). Though this evidence suggested that PA may play a significant role in the formation of urolithiasis, the relationship between the subtypes of PA and urolithiasis remained poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, hyperaldosteronism causes intracellular acidosis, which increases the absorption of citrate in the proximal tubules and induces hypocitraturia ( 9 , 23 ). A global epidemiological study showed that the prevalence of kidney stone disease ranges from 1.7% to 14.8% ( 24 ), while the prevalence of kidney stone disease in patients with PA is approximately 24% ( 12 ). Though this evidence suggested that PA may play a significant role in the formation of urolithiasis, the relationship between the subtypes of PA and urolithiasis remained poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive aldosterone is associated with secondary hyperparathyroidism, osteoporosis, calcium metabolic disorder, hypercalciuria ( 7 , 8 , 9 , 10 ), and acidic urine ( 11 ) and can promote the development of kidney stone disease. Clinically, patients with PA are reported to have a higher incidence of urolithiasis and larger kidney stones than patients with essential hypertension ( 12 ). However, the contribution of the different subtypes of PA to kidney stone disease remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic causes of hyperaldosteronism and pseudohyperaldosteronism with hypercalciuria and NL and/or NC are shown in Supplementary Table S3 . Studies have shown that individuals with hyperaldosteronism have a higher incidence of NL compared to the general population ( Chang et al, 2022 ). Hyperaldosteronism has also been associated with NC, thought to be related to factors including increased sodium excretion and resultant hypercalciuria, hyperphosphaturia, hypocitraturia, and hypokalemia-associated ammonia-medicated nephropathy ( Mittal et al, 2015 ).…”
Section: Genetic Causes Of Nephrolithiasis and Nephrocalcinosis In Ch...mentioning
confidence: 99%
“…Hyperaldosteronism has also been associated with NC, thought to be related to factors including increased sodium excretion and resultant hypercalciuria, hyperphosphaturia, hypocitraturia, and hypokalemia-associated ammonia-medicated nephropathy ( Mittal et al, 2015 ). Genetic hyperaldosteronism conditions associated with NL and/or NC are Familial hyperaldosteronism type I/Glucocorticoid-remediable aldosteronism ( CYP11B1 gene, AD inheritance, OMIM phenotype number 103900 ), Familial hyperaldosteronism type II ( CLCN2 gene, AD inheritance, OMIM phenotype number 605635 ), Familial hyperaldosteronism type III ( KCNJ5 gene, AD inheritance, OMIM phenotype number 613677 ), and Familial hyperaldosteronism type IV ( CACNA1H gene, AD inheritance, OMIM phenotype number 617027 ) ( Mittal et al, 2015 ; Chang et al, 2022 ). Pseudohyperaldosteronism type IIB/Gordon syndrome ( WNK4 gene, AD inheritance, OMIM phenotype number 614491 ) is associated with hypercalciuria and NL ( Mabillard and Sayer, 2019 ).…”
Section: Genetic Causes Of Nephrolithiasis and Nephrocalcinosis In Ch...mentioning
confidence: 99%
“…Instead, the putative reasoning invokes salt wasting with the attendant avid reabsorption of calcium and uric acid in type 4 RTA [62,63]. Further indirect evidence may be gleaned from patients with primary hyperaldosteronism who have increased risk for nephrolithiasis [64,65 ▪ ], in part from greater calcium excretion (due to volume expansion) but also hypocitraturia (from hypokalemia) [66].…”
Section: Are Uric Acid Stone Formers a Subpopulation Of Type 4 Renal ...mentioning
confidence: 99%